Microstructural comparison of the kinematics of discrete and continuum dislocations models - Sandfeld, Stefan; Po, Giacomo (Modelling and Simulation in Materials Science and Engineering, 2015)
The Continuum Dislocation Dynamics (CDD) theory and the Discrete Dislocation Dynamics (DDD) method are compared based on concise mathematical formulations of the coarse graining of discrete data. A numerical tool for converting from a discrete to a continuum representation of a given dislocation configuration is developed, which allows to directly compare both simulation approaches based on continuum quantities (e.g. scalar density, geometrically necessary densities, mean curvature). Investigating the evolution of selected dislocation configurations within analytically given velocity fields for both DDD and CDD reveals that CDD contains a surprising number of important microstructural details.
Keywords: coarse graining; continuum theory of dislocations; dislocation dynamics; microstructure